Akuntansi Hijau : Meta Analisis - Derisa, Putri; Purwanti, Meilani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Climate change and environmental degradation has driven companies to adopt more sustainable business practices, including the implementation of Green Accounting. This study aims to conduct a meta-analysis of Green Accounting implementation across various industrial sectors, based on 90 Scopus-indexed journals published between 2020 and 2024. The study focuses on identifying the influencing factors, commonly used indicators, research subjects, as well as the trends and conceptual foundations frequently addressed in the literature. This research uses a qualitative approach through thematic content analysis. Data were collected through literature review using purposive sampling of relevant articles. The findings indicate that regulatory frameworks, stakeholder pressure, and technological advancements are the main drivers of Green Accounting adoption. The most frequently used indicators include Green GDP, ESG reporting, and ISO 14001 certification. Common research subjects are found in the manufacturing, energy, and financial sectors. The study also shows that Green Accounting practices have evolved year by year, with increasing adoption, although they still face challenges such as lack of standardized reporting frameworks and limited application among SMEs. This study concludes that standard harmonization, regulatory support, and strategic integration of Green Accounting are essential for long-term corporate sustainability.